Research progress of traditional Chinese medicine on the treatment of diarrhea by regulating intestinal microbiota and its metabolites based on renal-intestinal axis - Zhou, Tong; Zhang, Yifan; Li, Zhaoyuan; Lu, Chunfeng; Zhao, Hong (Frontiers in Cellular and Infection Microbiology, 2024)
Intestinal microbiota and its metabolites are involved in many physiological processes of the human body and play a vital role in maintaining human health. The occurrence of kidney disease can cause intestinal microbiota imbalance, resulting in diarrhea. The change of intestinal microbiota and its metabolites content can aggravate renal function injury, which has a bidirectional regulating effect. The theory of renal-intestinal axis further clarified that the impaired renal function is related to the imbalance of intestinal microorganisms, and the impaired intestinal barrier is related to the accumulation of toxin products. Because of its unique therapeutic advantages, Traditional Chinese Medicine can treat diarrhea by enhancing the growth of beneficial bacteria, inhibiting pathogenic bacteria and immune regulation, and slow down the continuous deterioration of kidney disease. This paper focuses on the relationship between intestinal microbiota and its metabolites and diarrhea, the influence of Traditional Chinese Medicine on intestinal microbiota in the treatment of diarrhea, and the role of intestinal microbiota and its metabolites in the renal-intestinal axis. It provides a theoretical basis for Traditional Chinese Medicine to regulate intestinal microbiota and its metabolites based on the renal-intestinal axis theory to treat nephrology-induced diarrhea, and also provides a new idea and method for Traitional Chinese Medicine to treat nephrology-induced diarrhea.